Self-Disclosure in Criminal Justice: What Form Does It Take and What Does It Achieve? - Phillips, Jake (International journal of offender therapy and comparative criminology, 2018)
Self-disclosure, the act of therapists revealing something about themselves in the context of a professional relationship, has been linked with higher levels of effectiveness when used by correctional workers. However, it is poorly defined in both criminal justice policy and criminological research which has resulted in a lack of understanding about the potential risks and benefits to practice and practitioners. This article uses literature from other fields (namely, social work, counselling, and psychotherapy) to lay out what forms self-disclosure might take in the field of criminal justice. The article presents data that were generated as part of a larger project on emotional labour in probation practice in England. It analyses these data to argue that self-disclosure is used in two principle ways: to create and enhance a therapeutic relationship and in a more correctional way which is focused on criminogenic risk and need. We conclude by arguing that future research which seeks to identify a link between certain skills and effective outcomes needs to start with a much stronger definition of such skills as, otherwise, any effects are likely to be lost.